Law and social changes/ edited by J. S. Gandhi - Gandhi, J.S. (ed) (Jaipur, 1989)
This book consolidates in one com- pendium both theoretical and substan- tive perspectives on the relationship between law, society and social change. The papers contributed by both Indian and foreign authors deal with a variety of problems such as those concerning social cultural facilities and hindrances in carrying out change through law or those concerning the relevance of theo- retical models in explaining interactions and intersections between law and society. One message which clearly emerges is that whatever be the nature of legal improvisations, the questions of context, specificity of the issue involved and the socio-cultural matrix cannot be ignored.
Keywords: Laws and legislation